2019
DOI: 10.1080/1350293x.2020.1707360
|View full text |Cite
|
Sign up to set email alerts
|

Early learning opportunities for children at risk of social exclusion. Opening the black box of preschool practice

Abstract: Influenced by a growing number of longitudinal studies showing positive effects of preschool attendance, ECEC is framed as a potential equaliser of opportunities, especially to the benefit of children at risk of social exclusion and children from families with a migration background in particular. The preschool age is considered a crucial period for young children's language acquisition and there is consensus that stimulating and supportive teacher-child interactions in enriched classroom settings are paramoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Based on the prominence of the help interactions we observed, we argue that the IGs format challenges the idea that immigrant children are not stimulated to ask other children for help or to give support to another child (Peleman et al 2019). Indeed, seeking and providing help appear to be optimal scaffolds for the children to support each other in understanding tasks.…”
Section: Discussionmentioning
confidence: 82%
“…Based on the prominence of the help interactions we observed, we argue that the IGs format challenges the idea that immigrant children are not stimulated to ask other children for help or to give support to another child (Peleman et al 2019). Indeed, seeking and providing help appear to be optimal scaffolds for the children to support each other in understanding tasks.…”
Section: Discussionmentioning
confidence: 82%
“…Recent qualitative research conducted in four Flemish pre-schools educating children from poor families can illustrate this point. It demonstrated that in entry classes for 2.5- to three-year-olds, linguistic interactions between teachers and children, and among the children, provided few learning opportunities, which lacked, moreover, the high quality in language input and interaction that is needed to adequately develop academic language proficiency (Peleman et al, 2020; see also Roose et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Existing research in other European contexts highlights the problems of low quantity and quality of verbal and other interactions experienced by migrant or marginalised children (Peleman, Vandenbroeck, & Van Avermaet, 2020). This only compounds and reinforces the negative stereotypes and ideas educators hold over specific minority groups.…”
Section: Goals Values and The Role Of Ideas In Early Childhood Educamentioning
confidence: 99%